Cosmetic potential of marine fish skin collagen - Alves, Ana L. (2017)
Many cosmetic formulations have collagen as a major component because of its significant benefits as a natural humectant and moisturizer. This industry is constantly looking for innovative, sustainable, and truly efficacious products, so marine collagen based formulations are arising as promising alternatives. A solid description and characterization of this protein is fundamental to guarantee the highest quality of each batch. In the present study, we present an extensive characterization of marine-derived collagen extracted from salmon and codfish skins, targeting its inclusion as component in cosmetic formulations. Chemical and physical characterizations were performed using several techniques such as sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), Fourier Transformation Infrared (FTIR) spectroscopy rheology, circular dichroism, X-ray diffraction, humidity uptake, and a biological assessment of the extracts regarding their irritant potential. The results showed an isolation of type I collagen with high purity but with some structural and chemical differences between sources. Collagen demonstrated a good capacity to retain water, thus being suitable for dermal applications as a moisturizer. A topical exposure of collagen in a human reconstructed dermis, as well as the analysis of molecular markers for irritation and inflammation, exhibited no irritant potential. Thus, the isolation of collagen from fish skins for inclusion in dermocosmetic applications may constitute a sustainable and low-cost platform for the biotechnological valorization of fish by-products.